The Effectiveness of Music Therapy on Hand Function in Patients With Stroke: A Systematic Review of Randomized Controlled Trials - Huang, Wen-Hao; Dou, Zu-Lin; Jin, Hui-Min; Cui, Ying; Li, Xin; Zeng, Qing (Frontiers in Neurology, 2021)
Abstract Study Design: Systematic review. Objective: To evaluate the effect of music supported therapy for stroke patients' hand function. Methods: The databases used included Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, PubMed, Embase, Music Index, and Google Scholar. Studies published between January 2010 and August 2020 were included. The searching key terms included "music supported therapy", “music therapy”, "hand function", "hand dysfunction", "stroke", “ischemic”, “hemorrhagic”. The studies will be included if they were randomized controlled or controlled trials in adults who have hand function problems caused by stroke. Two independent assessors rated the study's quality and risk of bias by Cochrane collaboration's risk of bias tool. Results: Twelve studies met the inclusion criteria. Totally, the data included 615 stroke patients (345 male, 253 female) with the recruited time from 1.7 months to 3 years and the mean age of the participants were 61.09. Based on the Cochrane risk of bias tool, study quality ranged from 3 to 7 out of 7 points. Compared with the control group, outcomes like hand strength, range of joint motion, dexterity of hands, arm function and quality of life were significantly superior with music supported therapy. Five studies reported improved Dexterity of hands, and one study reported the improvement of range of motion and strength of patients' hands, which supported the therapy has positive effects on patients' hand function and improving their quality of life after the therapy. The therapy ranged over a period of 4 to 8 weeks, with an average duration of 30 minutes per session and an average of 3 times per week. Conclusion: Based on the results, music supported therapy could be a useful treatment for occupational therapists to use for stroke patients. However, it is necessary to develop a standardized MST treatment plan based on the different hand function stages according to the Brunnstrom stages so that we can design the standardized strategy for hand function improvement.